To find the numerical equivalent of \( 99 \cdot 9^{-6} \), we first need to evaluate \( 9^{-6} \).
The expression \( 9^{-6} \) is the same as \( \frac{1}{9^6} \).
Next, we need to calculate \( 9^6 \): \[ 9^6 = (3^2)^6 = 3^{12} \] Calculating \( 3^{12} \): \[ 3^2 = 9, \quad 3^3 = 27, \quad 3^4 = 81, \quad 3^5 = 243, \quad 3^6 = 729 \] Continuing, we compute \( 3^{12} \) as follows: \[ 3^6 = 729 \quad \Rightarrow \quad 3^{12} = 729 \times 729 = 531441 \] So, \( 9^6 = 531441 \) and thus: \[ 9^{-6} = \frac{1}{531441} \] Now, we multiply: \[ 99 \cdot 9^{-6} = 99 \cdot \frac{1}{531441} = \frac{99}{531441} \]
Next, we can simplify \( \frac{99}{531441} \):
- Factor \( 99 \): \[ 99 = 3^2 \cdot 11 \]
- Factor \( 531441 \) (as calculated previously, \( 531441 = 9^6 = (3^2)^6 = 3^{12} \)): \[ 531441 = 3^{12} \] Now we can rewrite the fraction: \[ \frac{99}{531441} = \frac{3^2 \cdot 11}{3^{12}} = \frac{11}{3^{10}} \] Calculating \( 3^{10} \): \[ 3^{10} = 59049 \quad (\text{since } 3^5 = 243 \text{ and } 3^{10} = 243^2 = 59049) \]
Thus, the final answer is: \[ \frac{11}{59049} \]
So, the numerical equivalent of \( 99 \cdot 9^{-6} \) is: \[ \boxed{\frac{11}{59049}} \]